Dysregulation of microRNA (miRNA) Due to Phthalate/Phthalate Metabolite Exposure and Associated Health Effects: A Narrative Review - Aamer Mohammed; Stephen L. Atkin; Edwina Brennan (Journal of Xenobiotics)
Phthalates, a group of synthetic non-persistent organic chemicals commonly used as solvents and plasticisers, have been associated with a range of detrimental health effects. These endocrine disrupting chemicals (ECDs) may exert their effects through epigenetic changes such as altered microRNA (miRNA) expression. miRNAs are short non-coding endogenous RNA transcripts that are preferentially expressed in various tissues and cell types and can circulate in body fluids, thereby regulating gene expression and acting as mediators for intercellular communication. As miRNAs mostly target protein-coding transcripts, they are involved in nearly all networks that regulate developmental and pathological processes. In this review, we provide an overview of human, in vivo and in vitro studies assessing altered miRNA expression due to phthalate exposure and their biological effects. Importantly, this study suggests that the mechanism of phthalate action may in part be mediated by epigenetic changes, affecting a large number of different proteins. This is indicative that alterations in miRNA expression induced by phthalate exposure are then implicated in a wide range of health conditions, including reproductive dysfunction, oncogenesis, metabolic disorders, and neurodevelopmental outcomes. Exposure to phthalates and their metabolites predominantly results in the upregulation of miRNAs. Dysregulation of miR-34a, miR-15b, miR-141, miR-184, miR-19a, miR-125, and miR-let-7 were observed across several studies. More research involving human participants combined with mechanistic studies integrating mRNA target analysis would be beneficial in understanding the downstream effects of phthalate exposure on gene expression and grasping the broader biological implications.